化简求值:2(ab눀-2a눀b)-3(ab눀-a눀b)+(2ab눀-2a눀b),其中a=2,b=1 急求!

在线=,求速度
2025-02-25 06:15:26
推荐回答(3个)
回答1:

2(ab²-2a²b)-3(ab²-a²b)+(2ab²-2a²b)
=2ab²-4a²b-3ab²+3a²b+2ab²-2a²b
=(2ab²-3ab²+2ab²)+(-4a²b+3a²b-2a²b)
=ab²-3a²b
=ab(b-3a)
将a=2,b=1代人
ab(b-3a)=2(1-6)=-10
如果帮到你,请记得采纳,O(∩_∩)O谢谢

回答2:

2(ab²-2a²b)-3(ab²-a²b)+(2ab²-2a²b)
=2ab²-4a²b-3ab²+3a²b+2ab²-2a²b
=ab²-3a²b
当a=2,b=1时
原式=ab²-3a²b=2-12=-10

回答3:

2(ab²-2a²b)-3(ab²-a²b)+(2ab²-2a²b)
去括号,得
2ab²-4a²b-3ab²+3a²b+2ab²-2a²b
=ab²-3a²b
=ab (b-3a)
把a=2,b=1代入上式,得
2ab²-4a²b-3ab²+3a²b+2ab²-2a²b
=ab²-3a²b
=ab (b-3a)
=2×1×(1-3×2)
=2×(-5)
= -10